High-dosage anti-fatigue high-solid-content emulsified asphalt regeneration mixture as well as preparation method and application thereof
High solid content emulsified asphalt is prepared by low-energy emulsification method, and the regenerated mixture achieves high performance under low temperature conditions, solving the energy consumption and greenhouse gas emission problems of high-temperature mixing in the prior art, and improving the fatigue resistance of the asphalt mixture and stability.
Patent Information
- Application Number
- CN202411522333.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
AI Technical Summary
The existing production technology of recycled asphalt mixture requires high temperature mixing, resulting in large energy consumption, high greenhouse gas emissions, and low dosage of waste asphalt recycling materials, making it difficult to meet high performance needs.
The low-energy emulsification method is used to prepare high-solid content emulsified asphalt, combined with low-temperature activator and molded crosslinking agent to form a large-scale anti-fatigue high-solid content emulsified asphalt regeneration mixture, achieving low-temperature mixing and excellent road performance.
Production of high-performance regenerated asphalt mixtures under low temperature conditions reduces energy consumption and greenhouse gas emissions, improves the fatigue resistance and stability of asphalt, and enhances the early strength and durability of the mixture.
Smart Images

Figure BDA0005108327490000151 
Figure BDA0005108327490000161
Abstract
Description
Technical Field
[0001] The invention belongs to the field of road engineering materials, and specifically provides a large-volume anti-fatigue high-solid content emulsified asphalt regeneration mixture and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] In recent years, with the vigorous development of highway industry, highway maintenance and reconstruction projects have gradually increased. A large amount of RAP materials are generated every year for highway maintenance and milling. Recycling waste asphalt pavement can not only promote the secondary utilization of non-renewable resources, but also reduce greenhouse gas emissions, and has good application prospects. The existing technology for producing recycled asphalt mixtures mainly adopts hot mixing technology. During production, asphalt and stone need to be heated to a very high temperature for mixing. During construction, they also need to be paved and rolled at high temperatures, which not only consumes a lot of energy but also emits a large amount of greenhouse gases and asphalt fumes, seriously affecting the environment. In addition, due to the performance attenuation, poor grading and uneven heating of RAP materials, the dosage of waste asphalt recycled materials (RAP) in the prior art is low. Therefore, there is an urgent need for a recycled asphalt mixture that can be prepared at a relatively lower temperature while increasing the RAP dosage.
[0004] Therefore, there is an urgent need to develop high-performance high-asphalt emulsified asphalt and high-solid content emulsified asphalt recycled mixtures with large dosage, fatigue resistance and excellent road performance that can achieve low-temperature mixing. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a high-solid emulsified asphalt regeneration mixture with high fatigue resistance that can achieve low-temperature mixing and excellent road performance. The high-solid emulsified asphalt prepared by the present invention can restore the high-temperature performance and crack resistance of aged asphalt. The production process of the mixture is green and environmentally friendly, and it has good mechanical properties, high-temperature stability, low-temperature crack resistance, water stability, and especially excellent fatigue resistance.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a large amount of fatigue-resistant high-solid emulsified asphalt recycled mixture, which is composed of the following raw materials in parts by weight: 5 to 8 parts of high-solid emulsified asphalt, 0.5 to 1 part of low-temperature activator, 0.05 to 0.08 parts of molding cross-linking agent, 45 to 100 parts of RAP material, 0 to 50 parts of new aggregate, and 0 to 5 parts of filler;
[0008] The high-solid emulsified asphalt is composed of a cationic slow-cracking and fast-setting amide emulsifier, 70# petroleum asphalt, hydrochloric acid and water, has a solid content of 80wt-90wt%, and is prepared by a low-energy emulsification method.
[0009] In some embodiments, the low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0010] In some embodiments, the molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether, and methyltrimethoxysilane, and the ratio of the three is 0.5:1:0.1.
[0011] In some embodiments, the RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of >30%, and a 0.075 sieve aperture pass rate ranging from 5-12%.
[0012] In some embodiments, the new aggregate is 10mm-15mm and 0mm-5mm limestone aggregates in a ratio of 25:20.
[0013] In some embodiments, the filler is limestone powder.
[0014] The second aspect of the present invention provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising:
[0015] Mix the emulsifier and water evenly, adjust the pH value to 2-2.3, and obtain a soap solution;
[0016] Add the soap solution at 60-65° C. to 70# petroleum asphalt at 120-130° C. and mix evenly to obtain high-solid content emulsified asphalt;
[0017] The RAP material and the low-temperature activator are mixed evenly, and then allowed to stand to obtain a mixed material for standby use;
[0018] The high solid content emulsified asphalt is heated to 60-80° C. for standby use;
[0019] Add new aggregate to the mixture, mix evenly, then add high-solid content emulsified asphalt, mix evenly, then add filler and molding cross-linking agent, mix evenly, and obtain.
[0020] In some embodiments, the mass ratio of the emulsifier to distilled water is 1:9-10.
[0021] In some embodiments, the mass ratio of the soap solution to 70# petroleum asphalt is 0.3:1.7-2.
[0022] More specifically, the following steps are included:
[0023] (1) mixing 1 part by weight of an emulsifier and 9 parts by weight of distilled water at 60° C. uniformly, and adjusting the pH value of the solution to 2-2.3 with hydrochloric acid to obtain a soap solution;
[0024] (2) adding 1.5 parts by weight of 60°C soap solution into 8.5 parts by weight of 120°C 70# petroleum asphalt at one time and stirring evenly at a stirring speed of 1000-1100 rpm for 10 min to obtain a high solid content emulsified asphalt;
[0025] (3) Add the RAP material to a mixing pot at room temperature, add a low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for later use;
[0026] (4) Heat the high solid content emulsified asphalt to 60-80°C to ensure good fluidity and set aside;
[0027] (5) Add new aggregate at room temperature into the mixing pot, stir for 30 seconds, then add high-solid content emulsified asphalt and stir for 60-90 seconds, continue to add filler and molding cross-linking agent, and then continue to mix for 60-90 seconds to obtain a large amount of fatigue-resistant high-solid content emulsified asphalt recycled mixture.
[0028] The third aspect of the present invention provides the use of the above-mentioned large-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture or the large-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture prepared by the above-mentioned method in the field of asphalt pavement construction or road engineering.
[0029] Beneficial effects of the present invention
[0030] (1) Compared with ordinary emulsified asphalt, the high-solid content emulsified asphalt of the present invention has an asphalt content of more than 80% and a water content significantly lower than that of ordinary emulsified asphalt. Using the high-solid content emulsified asphalt as a binder can solve the shortcomings of the traditional emulsified asphalt, such as the high water content of the traditional emulsified asphalt, the insufficient bonding effect of the asphalt, the poor water stability of the mixture, the road performance that does not meet the early strength requirements, the insufficient final road strength and the poor durability.
[0031] (2) The low-temperature activator of the present invention can quickly penetrate the asphalt layer on the surface of the RAP material, soften the aged asphalt on the surface of the RAP material, activate the aged asphalt, and better integrate it with the newly added asphalt to achieve "regeneration", playing the role of a binder. This effect overcomes the original problem that the aged asphalt can only be activated at high temperatures to achieve regeneration. The production process is green and environmentally friendly, with the characteristics of low cost, easy processing, and renewability.
[0032] (3) The molding crosslinking agent of the present invention includes one or more of Gemini ionic liquid, propylene glycol monomethyl ether, and methyl trimethoxysilane. The molding crosslinking agent is finally added to the mixture, and after contacting with the high-solid content emulsified asphalt, it can promote the uniform demulsification of the emulsified asphalt and form a crosslinking system, so that the mixture has a suitable curing molding time, and at the same time, consumes excess water during the molding and crosslinking process, ensuring that the mixture has good early strength and road performance.
[0033] (4) The powder-to-binder ratio of the RAP material of the present invention is 1.2-1.6, the pass rate of the 4.75 mm sieve hole is greater than 30%, and the pass rate of the 0.075 sieve hole is in the range of 5-12%. This design avoids the problem that the fine aggregate cannot effectively fill the mineral material intermittently, resulting in an increase in the void ratio, a decrease in the fatigue performance of the recycled mixture, and a serious impact on the durability. At the same time, this design method ensures that the mixture has a lower void ratio, thereby improving the low-temperature performance of the mixture.
[0034] In summary, the large-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture of the present invention can be produced at room temperature. Compared with the factory-mixed hot recycled mixture, it can effectively reduce the regeneration temperature, has significant energy-saving and emission reduction effects, and has comparable road performance to the factory-mixed hot recycled mixture. DETAILED DESCRIPTION
[0035] Preparation Example 1
[0036] The preparation method of high solid content emulsified asphalt includes:
[0037] (1) 1 part by weight of an emulsifier (the emulsifier is a cationic slow-cracking and fast-setting amide emulsifier provided by Jiangsu Jinyang New Material Technology Co., Ltd.) and 9 parts by weight of distilled water at 60° C. are stirred evenly, and the pH value of the solution is adjusted to 2-2.3 with hydrochloric acid to obtain a soap solution;
[0038] (2) 1.5 parts by weight of 60°C soap solution was added to 8.5 parts by weight of 120°C 70# petroleum asphalt (provided by Qinhuangdao Asphalt Plant of PetroChina Fuel Oil Co., Ltd.) and stirred evenly at a stirring speed of 1000-1100 rpm for 10 min to obtain a high-solid content emulsified asphalt.
[0039] Example 1
[0040] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0041] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.6 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0042] (2) 5 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0043] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 5 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 4.35 parts by weight of filler and 0.05 parts by weight of molding cross-linking agent are added, and then mixing is continued for 60-90 seconds to obtain a large-amount anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0044] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0045] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0046] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0047] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0048] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0049] Example 2
[0050] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0051] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.6 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0052] (2) 6 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0053] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 6 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 3.35 parts by weight of filler and 0.05 parts by weight of molding cross-linking agent are added, and then mixing is continued for 60-90 seconds to obtain a large-amount anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0054] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0055] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0056] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0057] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0058] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0059] Example 3
[0060] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0061] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.6 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0062] (2) 7 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0063] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 7 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 2.35 parts by weight of filler and 0.05 parts by weight of molding cross-linking agent are added and the mixture is stirred for 60-90 seconds to obtain a large amount of anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0064] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0065] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0066] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0067] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0068] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0069] Example 4
[0070] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0071] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.7 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0072] (2) 5 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0073] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 5 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 4.25 parts by weight of filler and 0.05 parts by weight of molding cross-linking agent are added, and then mixing is continued for 60-90 seconds to obtain a large-amount anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0074] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0075] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0076] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0077] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0078] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0079] Example 5
[0080] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0081] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.8 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0082] (2) 5 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0083] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 5 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 4.15 parts by weight of filler and 0.05 parts by weight of molding cross-linking agent are added and the mixture is stirred for 60-90 seconds to obtain a large amount of anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0084] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0085] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0086] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0087] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0088] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0089] Example 6
[0090] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0091] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.9 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0092] (2) 5 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0093] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 5 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 4.05 parts by weight of filler and 0.05 parts by weight of molding cross-linking agent are added, and then mixing is continued for 60-90 seconds to obtain a large-amount anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0094] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0095] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0096] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0097] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0098] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0099] Example 7
[0100] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0101] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.6 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0102] (2) 5 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0103] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 5 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 4.34 parts by weight of filler and 0.06 parts by weight of forming cross-linking agent are added and the mixture is stirred for 60-90 seconds to obtain a large amount of anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0104] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0105] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0106] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0107] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0108] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0109] Example 8
[0110] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0111] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.6 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0112] (2) 5 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0113] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 5 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 4.33 parts by weight of filler and 0.07 parts by weight of forming cross-linking agent are added, and the mixture is stirred for 60-90 seconds to obtain a large amount of anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0114] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0115] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0116] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0117] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0118] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0119] Example 9
[0120] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0121] (1) Add 45 parts of RAP material into a mixing pot at room temperature, add 0.6 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0122] (2) 5 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0123] (3) 45 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 5 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 4.32 parts by weight of filler and 0.08 parts by weight of molding cross-linking agent are added and the mixture is stirred for 60-90 seconds to obtain a large amount of anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0124] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0125] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0126] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0127] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0128] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0129] Example 10
[0130] This embodiment provides a method for preparing a large-volume anti-fatigue high-solid content emulsified asphalt recycled mixture, comprising the following steps:
[0131] (1) Add 46 parts of RAP material into a mixing pot at room temperature, add 0.6 parts of low-temperature activator, stir for 180 seconds, and then let it stand for 30 minutes for use;
[0132] (2) 5 portions of the high-solid emulsified asphalt prepared in Preparation Example 1 were heated to 60-80° C. to ensure good fluidity and set aside;
[0133] (3) 46 parts of new aggregate at room temperature are added to the mixing pot and stirred for 30 seconds. Then, 5 parts by weight of high-solid content emulsified asphalt are added to the mixing pot and stirred for 60-90 seconds. Then, 2.35 parts by weight of filler and 0.05 parts by weight of molding cross-linking agent are added, and then mixing is continued for 60-90 seconds to obtain a large-amount anti-fatigue high-solid content emulsified asphalt recycled mixture.
[0134] The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.5.
[0135] The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.1.
[0136] The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
[0137] The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:20.
[0138] The filler is limestone powder from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project.
[0139] Comparative Example 1
[0140] Compared with Example 1, the difference is that the high solid content emulsified asphalt is replaced by conventional emulsified asphalt. Conventional emulsified asphalt is prepared by a colloid mill and has a solid content of 60±2%. The emulsifier and asphalt used in conventional emulsified asphalt, as well as the emulsifier dosage and soap solution pH value are exactly the same as those of high solid content emulsified asphalt.
[0141] Comparative Example 2
[0142] Compared with Example 1, the difference is that 0 parts by weight of the molding cross-linking agent is added.
[0143] Comparative Example 3
[0144] Compared with Example 1, the difference is that 0 parts by weight of low-temperature activator is added.
[0145] Performance Testing
[0146] The regenerated asphalt mixtures prepared in Examples 1-10 of the present invention and Comparative Examples 1-3 were tested according to the standard of "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTGE20-2011).
[0147] The results are shown in Table 1.
[0148] Table 1 Performance test results of recycled asphalt mixtures of examples and comparative examples
[0149]
[0150]
[0151] Note: The strain is controlled to be 400 με.
[0152] As can be seen from the above data results, all the examples of large-amount anti-fatigue high-solid content emulsified asphalt recycled mixtures have good fatigue life results and large Marshall stability, indicating that the mixture has good strength.
[0153] Examples 1, 2, and 3 show that with the increase of the content of high-solid emulsified asphalt, the fatigue life of the mixture tends to increase, indicating that high-solid emulsified asphalt has the effect of promoting the softening of aged asphalt of RAP material and the bonding of new material under normal temperature conditions; Examples 1, 4, 5, and 6 show that with the increase of the content of low-temperature activator, the fatigue life of the mixture tends to increase. The low-temperature activator can quickly penetrate the asphalt layer on the surface of the RAP material, soften the aged asphalt on the surface of the RAP material, activate the aged asphalt, and better integrate with the newly added asphalt to achieve "regeneration", playing the role of a binder. This effect overcomes the original problem that the aged asphalt can only be activated at high temperature to achieve regeneration; Examples 1, 7, 8, and 9 show that with the addition of a molding cross-linking agent, the fatigue life of the mixture tends to increase, and the change is more obvious. The molding cross-linking agent can promote the uniform demulsification of the emulsified asphalt and form a cross-linking system, so that the mixture has a suitable curing molding time, and at the same time, it consumes excess water during the molding and cross-linking process, ensuring that the mixture has good early strength and road performance.
[0154] Comparative Example 1 uses common emulsified asphalt to prepare recycled mixture. Compared with Example 1, the mixture has a larger porosity, a 50% reduction in Marshall stability, a reduced strength, and an extremely low fatigue life. This shows that compared with common emulsified asphalt, high-solid emulsified asphalt has a significantly lower water content. Using it as a binder can solve the problems of poor water stability of the mixture, road performance that does not meet early strength requirements, insufficient final road strength, and poor durability due to the high water content of traditional emulsified asphalt.
[0155] Comparative Example 2 adds 0 parts of forming cross-linking agent to prepare recycled mixture, and the fatigue life of the mixture is reduced by 50% compared with that of Example 1. This shows that the forming cross-linking agent can promote the uniform demulsification of emulsified asphalt and form a cross-linking system, so that the mixture has good strength and fatigue life.
[0156] Comparative Example 3 adds 0 parts of low-temperature activator to prepare recycled mixture. Compared with Example 1, the fatigue life of the mixture is reduced by 40%. This shows that the low-temperature activator can soften the aged asphalt on the surface of the RAP material, activate the aged asphalt, and better integrate it with the newly added asphalt, playing the role of a binder. This effect overcomes the original problem that the aged asphalt can only be activated at high temperature, so that the mixture has good strength and fatigue life.
[0157] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture, characterized in that: The invention is composed of the following raw materials in parts by weight: 5-8 parts of high solid emulsified asphalt, 0.5-1 parts of low temperature activator, 0.05-0.08 parts of molding cross-linking agent, 45-100 parts of RAP material, 0-50 parts of new aggregate, and 0-5 parts of filler; The high-solid emulsified asphalt is composed of a cationic slow-cracking and fast-setting amide emulsifier, 70# petroleum asphalt, hydrochloric acid and water, has a solid content of 80wt-90wt%, and is prepared by a low-energy emulsification method.
2. The high-volume anti-fatigue and high-solid emulsified asphalt recycled mixture according to claim 1, characterized in that: The low-temperature activator is composed of fatty alcohol polyoxyethylene ether and dioctyl phthalate, and the mass ratio of fatty alcohol polyoxyethylene ether to dioctyl phthalate is 1:1.
5.
3. The high-solid content emulsified asphalt recycled mixture with high dosage and anti-fatigue properties as claimed in claim 1, characterized in that: The molding cross-linking agent is composed of Gemini ionic liquid, propylene glycol monomethyl ether and methyl trimethoxy silane, and the ratio of the three is 0.5:1:0.
1.
4. The high-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture according to claim 1, characterized in that: The RAP material comes from the middle and upper surface milling materials of the A1 section of the Zhangji Expressway reconstruction and expansion project, with a powder-to-rubber ratio of 1.2-1.6, a 4.75mm sieve aperture pass rate of more than 30%, and a 0.075 sieve aperture pass rate of 5-12%.
5. The high-solid content emulsified asphalt recycled mixture with high dosage and anti-fatigue properties as claimed in claim 1, characterized in that: The new aggregates are 10mm-15mm and 0mm-5mm limestone aggregates from the A1 section of the Zhangji Expressway Reconstruction and Expansion Project, with a ratio of 25:
20.
6. The high-volume anti-fatigue and high-solid emulsified asphalt recycled mixture according to claim 1, characterized in that: The filler is limestone powder from the A1 section of the Zhangji Expressway reconstruction and expansion project.
7. A method for preparing a large amount of fatigue-resistant and high solid content emulsified asphalt recycled mixture, characterized in that: include: Mix the emulsifier and water evenly, adjust the pH value to 2-2.3, and obtain a soap solution; Add the soap solution at 60-65° C. to 70# petroleum asphalt at 120-130° C. and mix evenly to obtain high-solid content emulsified asphalt; The RAP material and the low-temperature activator are mixed evenly, and then allowed to stand to obtain a mixed material for standby use; The high solid content emulsified asphalt is heated to 60-80° C. for standby use; Add new aggregate to the mixture, mix evenly, then add high-solid content emulsified asphalt, mix evenly, then add filler and molding cross-linking agent, mix evenly, and obtain.
8. The method for preparing a high-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture according to claim 7, characterized in that: The mass ratio of the emulsifier to distilled water is 1:9-10.
9. The method for preparing a high-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture according to claim 7, characterized in that: The mass ratio of the soap solution to 70# petroleum asphalt is 0.3:1.7-2.
10. Use of the high-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture as described in any one of claims 1 to 6 or the high-volume anti-fatigue and high-solid content emulsified asphalt recycled mixture prepared by the method described in any one of claims 7 to 9 in the field of asphalt pavement construction or road engineering.
Citation Information
Cited By
Milling material modification-based geocell filler and comprehensive performance evaluation method
CN120004556A
